Teachers’ Knowledge and Understanding of the Malaysian School-Based Oral English Assessment (Malaysian Journal of Learning and Instruction, 2011)
Purpose â€“ The paper sought to investigate TESL teachersâ€™ knowledge and understanding of the Malaysian School Based Oral English Assessment (SBOEA) after five years into its implementation in upper secondary ESL classrooms in Malaysian public schools Method â€“ The descriptive study involved a total of 80 TESL trained teachers from the 19 schools located in a district in Selangor, Malaysia. The study employed a three-prong strategy to collect data which included a questionnaire, semi structured interviews and document analysis. Findings â€“ The findings of the study indicated that there was a low compliance (58.7%) rate among teachers to the procedures laid out in the SBOEA Manual with regards to the implementation of SBOEA. The teachers also acknowledged their lack of knowledge and understanding of the SBOEA and a half of the teachers in the study admitted having problems with the scoring criteria. Some teachers highlighted that they felt the SBOEA lacked reliability and validity within and outside the schools. Significance â€“ The paper explores the possible implications of the study to the enhancement of the implementation of the School Based Oral English Assessment in Malaysian public schools.